Efektivitas Model Contextual Teaching and Learning (CTL) Terhadap Hasil Belajar IPAS Kelas V pada Materi Cahaya dan Sifatnya - Mutiara Dwi Puspita; Tita Tanjung Sari; Nisfil Maghfiroh Meita (IJPSE Indonesian Journal of Primary Science Education, 2025)
This research was conducted due to the low learning outcomes in the science subject at SDN Lalangon I. This research aims to determine the effectiveness of the contextual teaching and learning (CTL) model on the science learning outcomes of class V on the material of light and its properties. This research uses a quantitative approach of the experimental type. The research model used is true experimental with a pretest-posttest control group design. The sample in this research used a simple random sampling technique, namely 42 students of SDN Lalangon I which were divided into class VA as many as 21 people as the control class and class VB as many as 21 people as the experimental class. The data collection techniques used are observation, tests, and documentation to determine student learning outcomes in the learning process. The data analysis used includes prerequisite tests and hypothesis tests. Based on the data analysis that has been done, it can be seen that the average score of the experimental class is 80,47 and the control class is 66,19. From these results it can be seen that the average of the experimental class is higher than the control class. In addition, the hypothesis test through the t-test also showed a significant value (2-tailed) of 0,000 which means less than 0,05 (0,000 <0,05). Through the manual, the t-count value was obtained at 15,565 and the t-table was 2,016 which means the t-count value> t-table (15,565> 2,016), so Ha is accepted and Ho is rejected. In the n-gain score test, the mean n-gain percent value obtained a result of 67,56% which indicates an effective category. It can be concluded that the contextual teaching and learning (CTL) model is effective for the science learning outcomes of class V on the material of light and its properties.